The head of the Verb+Noun compounds in the Romance languages - Schroten, Jan (IBERIA: An International Journal of Theoretical Linguistics, 2011)
Verb+Noun compounds in Spanish and the other Romance languages have wellknown curious properties: (i) lack of nominalizing affix on the Verb; (ii) obligatory presence of the Noun, interpreted as the direct object of the Verb; (iii) interpretation as referring to persons or instruments able to perform the action expressed by the transitive verb. Compounds are uncommon in the Romance languages, whereas they are common and very productive in the Germanic languages. Verb+Noun compounds, however, are hardly found in the Germanic languages. The "Minimalist" model adopted in the analysis will provide the basic explanation: Verb+Noun compounds reflect the most "basic" syntactic structure, which can be used by default as a lexical process in the Romance languages, where "real compounding", incorporation of the noun into the verb, is out. The basic syntactic-lexical process is completed by another default process: the Verb+Noun is a lexical predicate in need of a subject, which is, again, provided "by default": [+HUMAN] or, by extension, [+INSTRUMENT] interpretation.